Collection, Description and Performance Evaluation of Herbaceous Medicinal Leguminous Plants of Kerala - Sunitha C (Department of Horticulture, College of Agriculture, 1996)
The present study titled 'Collection, description and performance evaluation of herbaceous medicinal leguminous plants of Kerala' was carried out at the Department of Horticulture, College of Agriculture, Vellayani from June 1995 to January 1996. Seeds of sixteen different species of herbaceous leguminous medicinal plants could be collected from authentic sources. Twelve different species with high rate of germination were raised and maintained till flowering and pod set in the medicinal plant garden of the Department of Horticulture. Detailed computerised descriptive blank supplemented with line drawings and authentic herbarium were prepared for each species. Cultural trial of eleven selected species of herbaceous leguminous medicinal plants, conducted as pure crop in open condition and as intercrop under shade in a twenty five year old coconut garden, indicated that under open condition the growth and yield are significantly superior in Abrus precatorius, Clitoria ternatea and Atylosia scarabaeoides than under shaded condition. Similarly, in Crotalaria verrucosa and Desmodium triangulare where leaves are the medicinally important plant part, the number of branches and number of leaves were significantly higher under open condition than under shade. The biomass yield of Crotalaria verrucosa was significantly superior under open condition than under shade. This revealed the limited chance of raising these five plant species as intercrops in coconut garden.